2016
DOI: 10.1590/s1677-5538.ibju.2014.0603
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with sacral neuromodulation for the treatment of lower urinary tract dysfunction in Brazil

Abstract: Objectives:We report on the short-term outcomes of sacral neuromodulation (SNM) for treatment of idiopathic lower urinary tract dysfunction in Brazil (procedures performed before 2014).Materials and Methods:Clinical data and surgical outcomes of patients who underwent SNM staged procedures were retrospective evaluated. Urological assessment included a focused medical history and physical examination, measurement of postvoid residual volumes, urodynamics, and bladder diaries. A successful test phase has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
2
1
0
Order By: Relevance
“…The early response of our patients to both types of treatment was good, with statistically significant improvements in all the voiding diary variables, which is comparable to other studies [ 10 , 11 , 13 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The early response of our patients to both types of treatment was good, with statistically significant improvements in all the voiding diary variables, which is comparable to other studies [ 10 , 11 , 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, UDS are also helpful to diagnose other causes of UI (especially stress UI) [12]. The early response of our patients to both types of treatment was good, with statistically significant improvements in all the voiding diary variables, which is comparable to other studies [10,11,13].…”
Section: Discussionsupporting
confidence: 84%
“…Rios et al reported no significant complications. However, they had 10.5% rate of infection rate in their series and 2% pain at IPG site [ 28 ]. In our series we also had no significant complications.…”
Section: Discussionmentioning
confidence: 99%